Loss and fragmentation of habitat for pastoral people and wildlife in East Africa: Concepts and issues - Reid, Robin S.; Thornton, Philip K.; Kruska, Russell L. (National Inquiry Services Center, 2004)
Little of the current focus on landscape fragmentation has focused on rangelands or pastoral lands. This paper investigates the existing evidence for causes and processes of fragmentation in pastoral lands and its effects of landscapes and peoples. More conceptual work is needed on the definition of loss and fragmentation, particularly efforts to clarify fragmentation from whose (or what's) perspective. Fragmentation and loss are caused by a suite of underlying demographic, economic, institutional, technological and policy, biological and climatic factors in east Africa, with property rights as a particularly important cause. These underlying causes often originate far from rangelands and drive more local causes like expansion of cropland and settlements and construction of fences and water points. Pastoral systems first fragment in wetter rangelands or in the key resource areas (wetlands, riverine areas) in drier rangelands. Ecological effects of fragmentation range widely across animal and plant populations, nutrient cycling and soils, with strong effects on animals with large body sizes. We have little understanding of the economic consequences of fragmentation and have a strong need to focus future research on valuing ecological services that affect human well-being, to gain a better picture of the complementarities and trade-offs land managers face during the process of fragmentation.